Efeito do exercício físico sobre a prenhez de ratas com hipertensão arterial crônica - Corrêa, Mikaela da Silva [UNESP] (2014)
Purpose: To evaluate the neonatal growth of the offspring of spontaneously hypertensive rats (SHR) subjected to treadmill exercise. Methods: SHR and Wystar Kyoto (WKY) rats were distributed into: sedentary group (SHR and WKY), exercised during pregnancy (SHR EXP and WKY EXP) and exercised previously and during pregnancy (SHR EXPP and WKY EXPP). During pregnancy, body weight, blood glucose, lactate and triglycerides levels and blood pressure were determined. At 10th day of life, body weight, blood glucose, and body and cranial length and hepatic triglycerides were analyzed. Results: There was no difference in body weight and lactate level during pregnancy, and number of pups among groups. The WKY EXPP group presented higher blood pressure than WKY and WKY EXP groups. SHR EXPP and WKY EXPP showed higher triglyceride level compared to groups trained in pregnancy and sedentary. SHR EXPP showed lower blood glucose than SHR and SHR EXP. There was no difference in the parameters of the newborns. In addition, body length was higher in WKY EXPP and SHR EXPP groups. Conclusion: The previous exercise was exhausting for the WKY strain. Exercise during pregnancy is not harmful to SHR rats and benefited the body length of offspring